Large scale calculation for holography using SSD - Sugiyama, Atsushi; Akiyama, Hayato; Hashikawa, Shingo; Shimobaba, Tomoyoshi; Kakue, Takashi; Ito, Tomoyoshi (Photonics Letters of Poland, 2014)
Computer based holography such as electro-holography and digital holography advances because the resolution of an imaging display and a sensing device such as a liquid crystal display (LCD) and a charge coupled device (CCD) becomes higher. A higher resolution of imaging device requires the more powerful computing system. On the other hand, a solid state drive (SSD) develops as a storage device of computers. We studied the effectiveness of SSD for a large-scale digital holography calculation. When the calculation data scale exceeds the main memory capacity, the SSD system showed better performance compared with the hard disk drive (HDD) system at computational speed and stability. Full Text: PDF References M. Stanley et al., "100-megapixel computer-generated holographic images from Active Tiling: a dynamic and scalable electro-optic modulator system", Proc. SPIE 5005, Practical Holography XVII and Holographic Materials IX, 247 (2003) CrossRef H. Sasaki, K. Yamamoto, Y. Ichihashi, T. Senoh, "Large size three-dimensional video by electronic holography using multiple spatial light modulators", Scientific Reports 4, Article number 04000 (2014) CrossRef T. Kozacki, G. Finke, P. Garbat, W. Zaperty, M. Kujawińska, "Wide angle holographic display system with spatiotemporal multiplexing", Opt. Express 20, 27473-27481 (2012) CrossRef T. Shimobaba et al., "In-line digital holographic microscopy using a consumer scanner", Scientific Reports 3, Article number 02664 (2013). CrossRef S.O.Isikman, A.Greenbaum, W.Luo,A.F.Coskun, A.Ozcan, "Giga-Pixel Lensfree Holographic Microscopy and Tomography Using Color Image Sensors", PloS one, 7(9), e45044 (2012) CrossRef T. Shimobaba et al., "Computational wave optics library for C++: CWO++ library", Comput. Phys. Commun. 183, 1124-1138 (2012) CrossRef